Transient Stability Analysis of Wind‐Thermal Bundled Systems Under Sequential Filter Removal - Di Che; Liang Wang; Xiufeng Han; Enyu Wei (Engineering Reports, 2025)
ABSTRACT Addressing issues such as insufficient transient stability and reduced transmission capacity in wind‐thermal bundled systems during DC blocking faults, this paper proposes a coordinated control strategy for wind‐thermal unit tripping under sequential filter removal. This strategy is based on the principle that retaining partial filters can enhance system stability and aims to improve system stability while reducing total unit tripping. By establishing a grid architecture model for a southwestern region, introducing static stability constraints, transient stability constraints, and filter capacity constraints as stability criteria, the study seeks to minimize the total wind‐thermal unit tripping under DC blocking faults. Simulation results demonstrate that when the filter removal amount is 2610 MVar, the total wind‐thermal unit tripping in this model is minimized to 3480 MW. This further proves that sequential filter removal can reduce unit tripping, enhance system stability, and improve transmission capacity. These findings provide an important basis for system operation optimization.